Assessment of workplace environmental contamination and occupational exposure to cisplatin and doxorubicin aerosols during electrostatic pressurized intraperitoneal aerosol chemotherapy. Issue 11 (November 2021) - Roussin, Fanny; Taibi, Abdelkader; Canal-Raffin, Mireille; Cantournet, Lucile; Durand-Fontanier, Sylvaine; Druet-Cabanac, Michel; El Balkhi, Souleiman; Maillan, Gaëlle
Abstract: Background: Electrostatic precipitation pressurized intraperitoneal aerosol chemotherapy (ePIPAC) is a novel approach for intraperitoneal drug delivery. As ePIPAC using cisplatin and doxorubicin is performed in an operating room, the challenge is to safely deliver the chemotherapeutic aerosol intraperitoneally while preventing exposure to healthcare workers. The objective of this study was to describe cisplatin and doxorubicin workplace environmental contamination and healthcare worker exposure during ePIPAC. Methods: Antineoplastic drugs concentrations of cisplatin and doxorubicin were measured in wipe samples from the operating room, and urine samples were collected from healthcare workers. The air samples were collected in order to detect Cisplatin contamination. Cisplatin was analysed by inductively coupled plasma–mass spectrometry and doxorubicin by ultra-high-performance liquid chromatography coupled with tandem mass spectrometry. Results: No trace of cisplatin was found in the air. Cisplatin and doxorubicin were detected on the operating room floor, surfaces, devices and personal protective equipment even after a cleaning protocol. No traces of cisplatin or doxorubicin were found in the urine samples. Conclusion: In this study, no internal contamination was found in the ePIPAC surgical team even after implementing two successive ePIPAC procedures. These results showed the effectiveness of the individual and collective protective measures applied. However, the cleaning procedure during ePIPAC should be respected to limit environmental exposure to chemotherapy to cisplatin and doxorubicin during ePIPAC.